Navigating the Challenges of an Adolescent Interview Using a Standardized Patient Video Case - Jane Goleman; Cynthia Holland-Hall (Association of American Medical Colleges, 2012)
Abstract The purpose of this resource is to introduce the medical student to medical interviewing of an adolescent. The adolescent interview poses a number of challenges due to the developmental changes that occur physically, emotionally, and socially as a child transitions to adulthood. Many adolescents feel that developmental pressure as they vacillate between dependence and independence. The adolescent interview is an opportunity to affirm healthy decisions and encourage adolescents to take more responsibility for their health and health behaviors. It is challenging because the physician must quickly assess the level of maturity, independence, and risk-taking for each adolescent. While the patterns of physical development are fairly consistent and predictable, numerous factors play a role in the progression of psychosocial development. The topics to be addressed in the assessment of an adolescent's health are numerous, personal, and may be considered controversial. The physician needs to develop an atmosphere of respect, trust and safety during the encounter, in order for the adolescent to feel comfortable sharing his/her concerns honestly. This resource combines a video of an adolescent-medicine physician interviewing an adolescent during her routine well-check and a standardized patient encounter in order to to introduce medical students to interviewing adolescents. The video portion is divided into three parts with discussion questions interspersed. Students are able to see how the physician sets the stage, uses the HEADSSS mnemonic effectively and conversationally, and mediates conflict between patient and her mother. The second half of the session, a student interviews a standardized adolescent and her parent. These materials were created in response to student feedback requesting to see an "expert" in adolescent medicine take a history from an adolescent. Prior to the creation of the video, each small group had a physician facilitator who demonstrated interviewing an adolescent standardized patient. The physicians represented a variety of medical specialties. The students' experiences varied depending on their small group facilitators. The art of the adolescent interview is difficult to demonstrate for those physicians who rarely see adolescents. The adolescent medicine physician who lectures to the class about adolescent development was willing to be video-taped. We used a standardized family (i.e., mother and daughter), and video-taped the physician as she would routinely respond to this same scenario in her practice.